Changing dynamics at the zero lower bound - Gregor Bäurle; Daniel Kaufmann; Sylvia Kaufmann; Rodney W. Strachan (Swiss National Bank, Study Center Gerzensee, 2016)
The interaction of macroeconomic variables may change as the nominal shortterm interest rates approaches zero. In this paper, we propose an empirical model capturing these changing dynamics with a time-varying parameter vector autoregressive process. State-dependent parameters are determined by a latent state indicator, of which the probability distribution is itself affected by the lagged interest rate. As the interest rate enters the critical zero lower bound (ZLB) region, dynamics between variables and the effect of shocks change. We estimate the model with Bayesian methods and take explicitly into account that the interest rate might be constrained in the ZLB region. We provide an estimate of the latent rate, i.e. the lower interest rate than the observed level which would be state- and modelconsistent. The endogenous specification of the state indicator permits dynamic forecasts of the state and the system variables. In an application to Swiss data, we evaluate state-dependent impulse-responses to a risk premium shock identified with sign-restrictions. Additionally, we discuss scenario-based forecasts and evaluate the probability of the system exiting the ZLB region based on the inherent dynamics only.
Keywords: C3; E3; 330; regime switching; time-varying probability; constrained variables